1992
DOI: 10.1007/bf02814580
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of biosynthesis of vermiculin and vermistatin inPenicillium vermiculatum

Abstract: Biosynthesis of vermiculin (1) and vermistatin (2) in Penicillium vermiculatum can be controlled by the carbon and nitrogen sources. Glucose and sucrose affect the levels of the two metabolites; cornsteep liquor influences the quality the biosynthesis. The concentrations of Fe3+ and Cu2+ ions also affect the biosynthesis, the effect being dependent on the type of carbon source utilized. The compounds capable of electron transport generally stimulate the production of 1 and 2 but do not influence the biosynthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…These compounds were not believed to be biosynthetically related due to their structural dissimilarity (Hara et al, 1989). For vermiculin and vermistatin, also structurally different compounds produced by unrelated pathways, sucrose, cornsteep liquor and lactic acid favored vermiculin, while glucose in the absence of cornsteep liquor favored vermistatin (Adamcova et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…These compounds were not believed to be biosynthetically related due to their structural dissimilarity (Hara et al, 1989). For vermiculin and vermistatin, also structurally different compounds produced by unrelated pathways, sucrose, cornsteep liquor and lactic acid favored vermiculin, while glucose in the absence of cornsteep liquor favored vermistatin (Adamcova et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…However, specific assays carried out for vermistatin have shown that the nitrogen source and the availability of some organic acids, such as malate and succinate, may notably influence the yield [ 30 , 31 ], which otherwise basically depends on duration of culturing. In most cases cultures are maintained for three weeks or longer, but available data are not sufficient to indicate the most appropriate length of the fermentation cycle.…”
Section: Methodology For Production and Extraction Of Funicone-relatementioning
confidence: 99%